2018
DOI: 10.1371/journal.pone.0207869
|View full text |Cite
|
Sign up to set email alerts
|

What’s going on in my baby’s mind? Mothers’ executive functions contribute to individual differences in maternal mentalization during mother-infant interactions

Abstract: Maternal mentalization refers to a mother’s capacity to understand mental-states of herself and her child and to regard her child as a psychological agent. In mother-infant interactions, this capacity is commonly conceptualized as maternal mind-mindedness, which can be divided into two dimensions: appropriate and nonattuned interpretations of the infants’ mental-states. Appropriate mind-mindedness refers to interpretations that seem to be compatible with the infant’s behaviors, whereas nonattuned mind-mindedne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 116 publications
(193 reference statements)
5
26
1
1
Order By: Relevance
“…First, effects were demonstrated in mothers of young children, who performed a visual search task that required attention control. Enhanced attention control may be part of the cognitive processes in mothers needed to provide care (Nittono et al, 2012), which corresponds with previous studies have shown that mothers' executive functioning is related to parenting behaviours and aspects important for parental care, such as an increased attention for and correct interpretation of infants' mental states (Crandall et al, 2015;Rutherford et al, 2018;Yatziv et al, 2018). Prior research showed that cute images of baby animals improved university students' performance on a visual search task (Nittono et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…First, effects were demonstrated in mothers of young children, who performed a visual search task that required attention control. Enhanced attention control may be part of the cognitive processes in mothers needed to provide care (Nittono et al, 2012), which corresponds with previous studies have shown that mothers' executive functioning is related to parenting behaviours and aspects important for parental care, such as an increased attention for and correct interpretation of infants' mental states (Crandall et al, 2015;Rutherford et al, 2018;Yatziv et al, 2018). Prior research showed that cute images of baby animals improved university students' performance on a visual search task (Nittono et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…Cute images may trigger a positive emotional state that is associated with approach motivation and a tendency toward systematic processing, resulting in enhanced attention control that may be part of the individual's cognitive processes needed to provide care (Nittono et al, 2012). Indeed, recent studies have shown that mothers' executive functioning is a determinant of parenting behaviours (Crandall, Deater-Deckard, & Riley, 2015), is related to a correct interpretation of the infants' mental states (Yatziv, Kessler, & Atzaba-Poria, 2018) and is associated with mothers' curiosity towards their infants' mental states (Rutherford et al, 2018).…”
mentioning
confidence: 99%
“…The moderating roles of contexts requiring regulation and stressful contexts in the links between maternal mentalization and EFs have only been considered in one study, which examined online mentalization (Yatziv, Kessler, et al, 2018). Thus, whether these modulating effects affect mothers’ stable representations of their child more broadly, or are restricted to maternal mentalization in real-time (which perhaps could be modified or “corrected” later, when reflecting offline in hindsight), remains to be tested.…”
Section: Child- and Family-related Contexts As Moderatorsmentioning
confidence: 99%
“…Maternal sense of coherence [ 14 ], anxiety [ 15 , 16 ], depression [ 16 ], social support [ 17 ], and fatalism [ 9 ] also have been associated with ECC. We have found no studies that examined the relationship between maternal executive function and ECC, although this factor affects children’s health and development [ 18 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Executive function, also known as executive control or cognitive control, is an effortful process of using a set of mental skills to concentrate on and pay attention to getting a task done. This is know as goal-directed behavior [ 18 ], rather than relying on instinct or intuition [ 19 , 20 ]. Maternal executive function is an important parenting behavior that children experience at a time when they rely on adequate caregiving [ 21 , 22 ] and which is linked with child neglect [ 23 , 24 ], a risk factor for ECC [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%